Usefulness of duckbill‐type anti‐reflux self‐expandable metal stents for distal malignant biliary obstruction with duodenal invasion: A pilot study. Issue 1 (9th March 2022) - Kobori, Ikuhiro; Katayama, Yasumi; Hayakawa, Fuki; Fujiwara, Takeshi; Kuwada, Masaru; Gyotoku, Yoshinori; Kitahama, Akihiro; Kusano, Yumi; Tamano, Masaya
Abstract: Objectives: Early obstruction of a self‐expandable metal stent placed for distal malignant biliary obstruction is more likely to occur in the presence of duodenal invasion. An anti‐reflux self‐expandable metal stent (ARMS) has been developed for the purpose of preventing duodenal fluid reflux into the bile duct. In this study, we evaluated the usefulness and safety of a duckbill‐type ARMS (D‐ARMS) in the situation of duodenal invasion. Methods: We retrospectively analyzed 10 consecutive patients who received D‐ARMS for distal malignant biliary obstruction with duodenal invasion. We evaluated non‐occlusion cholangitis, recurrent biliary obstruction (RBO), and adverse events after D‐ARMS placement. Results: There were no cases of non‐occlusion cholangitis. RBO was observed in 2 patients (20%), and time to RBO was 236 days and 117 days, respectively. The causes of RBO were overgrowth and sludge formation. The median time to RBO was 382 days (range, 117–382 days). Only one adverse event was observed (cholecystitis). Conclusions: D‐ARMS shows potential as an optimal ARMS.